A systematic review evaluating the impact of online or blended learning vs. face‐to‐face learning of clinical skills in undergraduate nurse education. (19th August 2014) - McCutcheon, Karen; Lohan, Maria; Traynor, Marian; Martin, Daphne
Abstract Aim To determine whether the use of an online or blended learning paradigm has the potential to enhance the teaching of clinical skills in undergraduate nursing. Background The need to adequately support and develop students in clinical skills is now arguably more important than previously considered due to reductions in practice opportunities. Online and blended teaching methods are being developed to try and meet this requirement, but knowledge about their effectiveness in teaching clinical skills is limited. Design Mixed methods systematic review, which follows the Joanna Briggs Institute User guide version 5. Data sources Computerized searches of five databases were undertaken for the period 1995–August 2013. Review methods Critical appraisal and data extraction were undertaken using Joanna Briggs Institute tools for experimental/observational studies and interpretative and critical research. A narrative synthesis was used to report results. Results Nineteen published papers were identified. Seventeen papers reported on online approaches and only two papers reported on a blended approach. The synthesis of findings focused on the following four areas: performance/clinical skill, knowledge, self‐efficacy/clinical confidence and user experience/satisfaction. The e‐learning interventions used varied throughout all the studies. Conclusion The available evidence suggests that online learning for teaching clinical skills is no less effective than traditional means. Highlighted by this review is the lack of available evidence on the implementation of a blended learning approach to teaching clinical skills in undergraduate nurse education. Further research is required to assess the effectiveness of this teaching methodology.